PENERAPAN STEAM DALAM EKSPERIMEN FILTRASI AIR BERSIH SEDERHANA DI SD NEGERI BABAKAN UNTUK MENINGKATKAN PEMAHAMAN SAINS - Kailla Cahaya Islami; Kohar Pradesa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Clean water is a basic necessity essential for human life. However, challenges in meeting this need are increasing due to environmental pollution and limited access to water treatment technologies, especially in rural areas. A simple water filtration experiment based on Project Based Learning (PjBL) with a STEAM (Science, Technology, Engineering, Arts, Mathematics) approach was implemented at SD Negeri Babakan to enhance students' understanding of water pollution and its treatment. Through this experiment, students not only learn the theory of filtration but also actively engage in designing and evaluating water filtration devices. This research aims to explore the impact of project-based learning on developing students' critical, creative, and collaborative thinking skills, as well as their environmental awareness. The findings indicate that this approach effectively improves students' understanding of scientific concepts and their practical application in daily life.